2018
DOI: 10.1186/s12912-018-0276-0
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learnt in recruiting disadvantaged families to a birth cohort study

Abstract: BackgroundDental decay in early childhood can be prevented by a model based on shared care utilising members of primary care team such as Child and Family Health Nurses (CFHNs) in health promotion and early intervention. The aims of this study were to identify the facilitators and barriers faced by CFHNs in recruiting research participants from disadvantaged backgrounds to a birth cohort study in South Western Sydney, Australia.MethodsChild and Family Health Nurses recruited mothers-infants dyads (n = 1036) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…This is also the case in our study. Previous studies have identified barriers to participation in birth cohorts, such as limited language or literacy skills, burden imposed by excessive information or demanding study procedures, and lack of cultural sensitivity among study personnel [27, 28]. The assessment of reasons for non-participation in the KUNO-Kids study yielded similar findings.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This is also the case in our study. Previous studies have identified barriers to participation in birth cohorts, such as limited language or literacy skills, burden imposed by excessive information or demanding study procedures, and lack of cultural sensitivity among study personnel [27, 28]. The assessment of reasons for non-participation in the KUNO-Kids study yielded similar findings.…”
Section: Discussionmentioning
confidence: 65%
“…On the other hand, experience from other cohorts suggests that at least some barriers to study participation can be overcome by intensified recruitment efforts [27, 29, 30]. Considering the low participation rate in our study, we decided to modify the recruitment strategy in the next phase of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Public hospitals were chosen with an intent to recruit under-represented socio-economically disadvantaged population groups and also because the entire Sydney region cannot be covered geographically [28]. Child and Family Health Nurses (CFHNs) during their first post-natal home visit (four to six weeks postpartum) recruited the mother-infant dyads [27,29]. The CFHNs described the study to the mothers and obtained their written informed consent.…”
Section: Samplementioning
confidence: 99%
“…Written consent was obtained at this time and interpreter services for non-English speakers were provided along with written material in the respective languages of the women [28]. This study was conducted in public hospitals in order to better recruit the under-represented population groups found in Sydney including socioeconomically disadvantaged and ethnically diverse groups [29].…”
Section: Study Populationmentioning
confidence: 99%